2006
DOI: 10.1038/sj.ejcn.1602379
|View full text |Cite
|
Sign up to set email alerts
|

Fat-soluble vitamins in breast-fed preterm and term infants

Abstract: Objective: To examine the supply and status of fat-soluble vitamins in very low birth weight (VLBW) infants compared to a reference group of normal birth weight (NBW) infants. Design: A longitudinal study of VLBW infants in the early neonatal period. Blood samples were drawn at 1 week of age and at discharge from hospital. Plasma was analyzed for the fat-soluble vitamins: retinol, 25-OH-vitamin D, a-tocopherol and phylloquinone (vitamin K 1 ) using high-performance liquid chromatography. Subjects: A total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
20
0
2
Order By: Relevance
“…In 10 vegetarian children, the mean concentration was 1.07 µmol/L. In 32 Norwegian breast-fed infants at one month of age (Henriksen et al, 2006), the median plasma retinol concentration was 0.72 µmol/L (IQR 0.62 to 0.86 µmol/L).…”
Section: Vitamin Amentioning
confidence: 99%
“…In 10 vegetarian children, the mean concentration was 1.07 µmol/L. In 32 Norwegian breast-fed infants at one month of age (Henriksen et al, 2006), the median plasma retinol concentration was 0.72 µmol/L (IQR 0.62 to 0.86 µmol/L).…”
Section: Vitamin Amentioning
confidence: 99%
“…Previous studies have Vitamin A and E status in preterm infant S Kositamongkol et al consistently shown high incidence of fat-soluble vitamin deficiency, especially vitamin A in VLBW infants. 15 In breast-fed preterm and term infants, Henriksen et al 7 reported that plasma retinol concentrations in preterm infants at discharge were significantly lower than term counterparts at 4 weeks of age. However, there was no significant difference in plasma a-tocopherol between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…8 Despite vitamin supplementation, a high incidence of vitamin A and vitamin E deficiency in VLBW infants has been reported. 7,[9][10] Such data are reported from developed countries that may differ from developing countries as Thailand in terms of nutritional and socioeconomical status and genetic factors. We, therefore, conducted a study with the aim to assess the vitamin A and vitamin E status of VLBW infants in our institution and to define the associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma tocopherol levels were within the reference range (14-50 µM). Dietary intake was estimated from parenteral nutrition, human milk, formulas and oral supplements (2 mg per day as an oral multivitamin plus 15 mg/day as alphatocopherol) [50]. In 2002, the Expert Panel of the American Society for Nutritional Sciences recommended a minimum of 2 mg and a maximum of 8.0 mg alpha-tocopherol/100 kcal in preterm infant formulas, and the vitamin E/PUFA ratio (mg alpha-tocopherol/g total PUFA) should exceed 1.5 mg/g [8].…”
Section: Recommendations For Vitamin Ementioning
confidence: 99%